2018
DOI: 10.1007/s00248-018-1203-3
|View full text |Cite
|
Sign up to set email alerts
|

Marked Succession of Cyanobacterial Communities Following Glacier Retreat in the High Arctic

Abstract: Cyanobacteria are important colonizers of recently deglaciated proglacial soil but an in-depth investigation of cyanobacterial succession following glacier retreat has not yet been carried out. Here, we report on the successional trajectories of cyanobacterial communities in biological soil crusts (BSCs) along a 100-year deglaciation gradient in three glacier forefields in central Svalbard, High Arctic. Distance from the glacier terminus was used as a proxy for soil age (years since deglaciation), and cyanobac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 60 publications
(105 reference statements)
0
25
0
Order By: Relevance
“…The frozen habitats might then provide a pool of propagules for microbial colonization, which is supported by the fact that microbial assemblages in ice and soil habitats are relatively similar (Kaštovská et al, 2007;Wynn-Williams, 1990). This has recently been supported by , Pessi, Pushkareva, et al (2018), who found that cyanobacteria transported from nearby glacial environments are the main colonizers of ice-free soil following glacier retreat. On a worldwide scale, various factors regarding longrange dispersal of microorganisms between and across both polar regions have also been identified: Atmospheric circulation can transport spores or even cells over large distances (Elster, Delmas, Petit, & Reháková, 2007;González-Toril et al, 2009), and marine migratory birds, which are known to cross the two hemispheres (Schlichting, Speziale, & Zink, 1978), may introduce alien strains.…”
mentioning
confidence: 69%
See 3 more Smart Citations
“…The frozen habitats might then provide a pool of propagules for microbial colonization, which is supported by the fact that microbial assemblages in ice and soil habitats are relatively similar (Kaštovská et al, 2007;Wynn-Williams, 1990). This has recently been supported by , Pessi, Pushkareva, et al (2018), who found that cyanobacteria transported from nearby glacial environments are the main colonizers of ice-free soil following glacier retreat. On a worldwide scale, various factors regarding longrange dispersal of microorganisms between and across both polar regions have also been identified: Atmospheric circulation can transport spores or even cells over large distances (Elster, Delmas, Petit, & Reháková, 2007;González-Toril et al, 2009), and marine migratory birds, which are known to cross the two hemispheres (Schlichting, Speziale, & Zink, 1978), may introduce alien strains.…”
mentioning
confidence: 69%
“…; Pessi, Pushkareva, et al. ). In contrast, in alpine habitats, the community composition appears to shift markedly along chrono‐sequences, indicating that each soil environment selects for its phototrophic community (Frey, Bühler, Schmutz, Zumsteg, & Furrer, ).…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Also equatorial, glacier-fed streams present unique hydraulic patterns when compared to temperate regions, and taxon richness in glacier-fed streams of the Ecological Reserve of Antisana (Ecuador) will be significantly reduced following glacier shrinking (Cauvy-Fraunié et al, 2013). But these equatorial glaciers are also unique ecosystems and may be sources of nutrients and first migrants in cold water streams (Bagshaw et al, 2013;Dresch et al, 2019;Pessi et al, 2018).…”
mentioning
confidence: 99%